Case report: Anorexia nervosa and unspecified restricting-type eating disorder in Jewish ultra-orthodox religious males, leading to severe physical and psychological morbidity - Laufer, Sofia; Herman, Estee; Serfaty, David; Latzer, Yael; Ashkenazi, Rachel; Attias, Orna; Oren, Sinai; Shimomi, Meirav; Uziel, Moria; Enoch-Levy, Adi; Witztum, Eliezer; Stein, Daniel (Frontiers in Psychiatry, 2023)
Background: Young Jewish Ultra-Orthodox women usually show less disturbances in body image and eating in comparison to less religious communities. By contrast, problems with eating are highly unknown and unrecognized in Jewish Ultra-Orthodox males. Aim: To investigate whether in Ultra-Orthodox males, restricting-type AN (AN-R) with highly obsessional physical activity and unspecified restricting eating disorder (ED) in the context of obsessive-compulsive disorder (OCD) would lead to severe physical and emotional morbidity. Results: The study included two groups: the first, 3 adolescents with AN-R developing severely increased ritualized obsessional physical activity in addition to restricting eating, requiring inpatient treatment because of severe bradycardia. These youngsters ignored the severity of their obsessional physical activity, continuing with it in hospital despite their grave medical condition. One student began extensive training for triathlon, whereas another student, upon remitting from AN, developed severe muscle dysmorphia. These findings suggest that young Ultra-Orthodox males with AN may develop obsessional physical activity to increase their muscle mass rather than to lose weight Another four Jewish Ultra-Orthodox males developed malnutrition in the context of severe OCD, with no evidence of dieting or body-image disturbances. These individuals developed highly obsessional adherence to different Jewish religious rules, including prolonged praying, asceticism, and overvalued strict adherence to Jewish Kashrut rules of eating, leading in all cases to severe food restriction. They were highly unaware of their severe weight loss and required hospitalization because of severe physical disturbances associated with malnutrition. Moreover, most did not cooperate with their treatment, and their ED-related obsessionality was mostly resistant to psychopharmacotherapy. Conclusions: Owing to their highly ritualistic rigid way of life, combined with the need for excellency in studying, Jewish Ultra-Orthodox adolescent males with AN might be at a specific risk of developing severe physical disturbances if their illness is associated with highly perfectionistic obsessional physical activity. Second, Jewish Ultra-Orthodox religious males with OCD might be at a specific risk for severe undernutrition, as their rigid relentless observance of Jewish everyday laws might highly interfere with their eating.